Handbook of flotation reagents chemistry, theory and practice - Bulatovic, Srdjan M. (Amsterdam Elsevier, 2015)
Handbook of Flotation Reagents: Chemistry, Theory and Practice is a condensed form of the fundamental knowledge of chemical reagents commonly used in flotation and is addressed to the researchers and plant metallurgists who employ these reagents. This book consists of three distinct parts: part 1 provides detailed description of the chemistry used in mineral processing industry; part 2 describes theoretical aspects of the action of flotation reagents, while part 3 provides information on the use of reagents in over 100 operating plants treating Cu, Cu/Zn, Cu/Pb, Zn, Pb/Zn/Ag, Cu/Ni and Ni ores.--Provided by publisher.
Electronic reproduction.
Keywords: Flotation reagents -- Handbooks, manuals, etc; Electronic books